AUGMENTED REALITY FOR VISITING GUIDE TO THE LIBRARY ROOM - Sasti Diana Putri Yanova; Muhammad Irwan Padli Nasution (Jurnal Teknik Informatika (Jutif), 2022)
Libraries are one of the places that have an important role in the world of education, in this era libraries are often overlooked because technology is very helpful for daily human activities, causing a lack of interest in reading from humans themselves. The problem that exists in the public library of campus IV UINSU Medan is how visitors have difficulty finding shelves or finding the books they need so they need directives from officers. Augmented reality technology in this application uses the markerless method to bring up 3D objects from the public library building of the campus IV UINSU Medan. The results of this application program are called digital libraries which can make it easier for users to find rooms as well as books available in the library, without the need to ask the security guards or officers. Based on the blackbox testing that has been done, this application has been running as expected by the application developer. This application works runs on the android operating system and work offline, which makes its easy for users to use it.